DESIGN, SYNTHESIS, AND BIO PROFILING OF 2, 3-DIHYDROQUINAZOLIN-4(1H)-ONE DERIVATIVE AS TYPE II DIABETES AGENTS: A COMPREHENSIVE IN SILICO, IN VITRO, AND IN VIVO STUDY - MATHEW, MINCY; KILIMOZHI, D.; M. MATHEWS, SANTHOSH; SMITH, ANTON (International Journal of Applied Pharmaceutics, 2024)
Objective: Diabetes mellitus is a significant global health challenge, with Type 2 Diabetes Mellitus (T2DM) being a leading cause of mortality worldwide, demanding the need for effective interventions by developing innovative therapeutic strategies or novel antidiabetic agents. This study explores in silico, in vitro, and in vivo approaches to identify the most potent 2,3-Dihydroquinazolin-4(1H)-One derivative molecule with antidiabetic activity. Methods: Eleven new derivatives were designed, studied in silico to identify the most promising compounds, synthesized, studied spectrally to describe them, and evaluated for both in vitro and in vivo investigations. Alpha amylase and alpha-glucosidase inhibitory activities were investigated in vitro. The endogenous suppression of glucose synthesis in Hepatoblastoma cell line 2(HepG2) cells and the in vitro glucose absorption assay on cultivated L6 cell lines were conducted. To assess the ability of the newly synthesized compounds to prevent diabetes, in vivo investigations were conducted on Streptozotocin (STZ)-induced diabetic rats and the effects on various biochemical parameters were identified. Results: Leveraging computational methods, the QZ9 molecule was identified with stable interactions with key biomolecules associated with T2DM. Subsequent in vitro assays confirmed the inhibitory effects of QZ2, QZ8, and QZ9 on alpha-amylase and alpha-glucosidase activities, suggesting their potential as enzyme inhibitors. Additionally, QZ8 and QZ9 demonstrated enhanced glucose uptake and production inhibition in HepG2 cells, indicating their role in improving glucose homeostasis. In vitro, the top-ranked molecules QZ2, QZ8, and QZ9 were analyzed to validate the in silico findings and assess their potential as therapeutic agents for T2DM. The inhibition of α-amylase activity by QZ2, QZ8, and QZ9 was dose-dependent, with maximum inhibition observed at 1000 µg/ml: 57.33% for QZ2, 52.21% for QZ8, and 87.16% for QZ9. Similarly, α-glucosidase inhibition at 1000 µg/ml was 59.96% for QZ2, 53.50% for QZ8, and 81.51% for QZ9. Both QZ8 and QZ9 significantly increased glucose uptake and inhibited glucose production in HepG2 cells, with maximum glucose production inhibition at 100 µg/ml: 62.22% for QZ8 and 62.35% for QZ9. These findings suggest that QZ8 and QZ9 contribute to glucose homeostasis. QZ9 demonstrated superior enzyme inhibition compared to QZ2 and QZ8, with α-amylase and α-glucosidase inhibition up to 87.16% and 81.51%, respectively, at 1000 µg/ml. In vivo investigations in Diabetic rat models further confirmed the efficacy of these compounds by showing significant reductions in blood glucose levels. These results suggests the potentiality of QZ9 as a promising novel Antidiabetic agent. Conclusion: Combining computational predictions with experimental validations, this integrated approach highlights the promise of 2,3-Dihydroquinazolin-4(1H)-One derivative QZ9 as a novel antidiabetic agent, warranting further investigation for clinical translation.